VD_FINDINFO Jug / 2017 / 343 vom 3. April 2017 - VD Tribunal cantonal (2017)
EMPLOYÉ PUBLIC, RÉSILIATION, INTERPRÉTATIONSENS GÉNÉRAL, ENSEIGNANT, PROPORTIONNALITÉ, TORT MORAL | 328 CO, 29 Cst., 9 Cst., 19 LPers-VD, 5 LPers-VD, 59 LPers-VD, 72 LS, 79 LS, 80 LS, 108 RLS